Алгоритм мониторинга метода двухфакторной аутентификации на основе системы PassWindow - Евсеев, Сергей Петрович; Абдуллаев, Вугар Гаджимахмудович (ПП "Технологічний Центр", 2015)
Рассматриваются основные методы построения систем двухфакторной аутентификации. Анализируется система PassWindow, обеспечивающая двухфакторную аутентификацию на уникальной способности наложения физического шаблона знаков предполагаемого получателя и шаблона штрих-кода, получаемых через электронно-сетевые устройства пользователей. Предлагается практический алгоритм мониторинга данной системы, способный получить уникальный шаблон штрих-кода за фиксированное количество перехватов.

The paper deals with the basic methods of constructing a two-factor authentication system based on cryptographic mechanisms for ensuring the cryptographic security of the authenticators formed. Risk assessment of various methods of online attacks against various two-factor authentication systems is carried out. The PassWindow system, which provides two-factor authentication on the unique ability of the matrix particles to transmit information in a way that it is deciphered only when imposing the physical template of characters of the intended recipient and barcode template, obtained through electron-network devices of users is considered. Resistance to the analysis is provided by a unique generation of barcode template of the card as unique statistical images, a sequence of characters or a more extended animated version. The object of the research is the process of improving the integrity and authenticity of data packets in security protocols of banking transactions based on two-factor authentication methods. The subject of the study are control methods and algorithms of the integrity and authenticity of data packets in security protocols of banking transactions based on two-factor authentication methods. The aim is to increase the integrity and authenticity of data packets in security protocols of banking transactions, threat assessment of two-factor authentication methods. A comparative analysis of various two-factor authentication systems with the PassWindow system in withstanding various Internet attack scenario is performed.
Monitoring algorithm of two-factor authentication method based on PassWindow system
Keywords: двухфакторная аутентификация; онлайн-атаки; социальная инженерия; two-factor authentication; online attacks; social engineering